Development and psychometric validation of the student mathematical commitment scale - Retchelle P. Sangco; Leorence C. Tandog; Jonald L. Pimentel (International Journal of Evaluation and Research in Education (IJERE), 2026)
Commitment plays a significant role in shaping engagement and self-regulation in learning, yet no standard tool exists to measure students’ learning commitment, especially in mathematics. This study aimed to develop the first validated scale for mathematical commitment. Using an exploratory-sequential mixed methods design, the study began with qualitative in-depth interviews (IDIs) to create the first version of the student mathematical commitment scale (SMCS) with 79 items. The quantitative phase employed exploratory and confirmatory factor analyses to establish the scale’s validity and reliability, resulting in a refined 24-item version, with four confirmed dimensions. These dimensions: strategic learning engagement (SLE), affective learning engagement (ALE), learning engagement resilience (LER), and positive learning mindset (PLM) provide a holistic view of mathematical commitment, encompassing the cognitive, emotional, and psychological aspects of students’ learning behavior. The findings provide a foundational understanding of mathematical commitment, suggesting the practical use of the scale in curriculum design, interventions, and student support with the goal of improving student learning outcomes.